2008
DOI: 10.1111/j.1365-2753.2007.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of breast cancer and lymph node metastatic status with tumour markers using logistic regression models

Abstract: TPS may be useful in the detection of primary breast cancer, while sIL-2R may be useful in lymph node metastasis prediction. The combination of more than one biomarker with logistic regression model can improve the predictive sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…It is known from the literature that TPS serum levels increased in other neoplastic diseases. Hwa et al [15] found that the TPS serum level was elevated in patients with breast cancer and showed the best predictive value among analyzed tumor markers, with a sensitivity of 80%. Assessment of TPS serum levels also appeared effective in improvement early diagnosis of recurrent ovarian cancer [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from the literature that TPS serum levels increased in other neoplastic diseases. Hwa et al [15] found that the TPS serum level was elevated in patients with breast cancer and showed the best predictive value among analyzed tumor markers, with a sensitivity of 80%. Assessment of TPS serum levels also appeared effective in improvement early diagnosis of recurrent ovarian cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that TPS reflects the activity of tumor growth, however its clinical utility in cancer diagnosis is controversial [11,12,13,14]. In some studies, TPS has been found to be superior to CA19-9 [15,16], but inferior in others [14,17]. The aim of our study was to compare the clinical usefulness of CA19-9, neopterin and TPS serum levels in differential diagnosis of PA and CP as well as to assess their possible prognostic value.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue polypeptide specific antigens (TPS), which measures M 3 antigenic determinant associated with human cytokeratin 18, is a marker of tumor cell activity in contrast to markers related to tumor burden (Rydlander et al, 1996). In breast cancer management, there is an improved effectiveness can be seen when TPS is used in combination with CA15-3 (Hwa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is CA15.3, which has proven useful in patients with metastatic breast cancer, when response to systemic therapy cannot be assessed (4,7). The combination of TPS, CA15-3 and IGFBP-3 increases sensitivity to 85%, and thus improves predictive ability (8). Increased CEA concentrations reflect higher risk in patients with adenocarcinomas (ACs), but not in those with squamous cell carcinomas (SCCs).…”
Section: Introductionmentioning
confidence: 99%